2006
DOI: 10.1002/pd.1627
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis in myotonic dystrophy type 1. Thirteen years of experience: implications for reproductive counselling in DM1 families

Abstract: In our series, no significant deviation of the 50% expected frequency of transmission in autosomal dominant disorder was seen. We show that when the disease is transmitted by a male, the mean intergenerational variation is minimal (mean = 56 CTG, SD = 177 CTG). However, this does not occur in the affected mothers, where the mean intergenerational expansion is very high (mean = 948 CTG, SD = 815 CTG) and the difference is statistically significant (t-Student p < 0.0001). Our data have important implications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 30 publications
0
25
0
2
Order By: Relevance
“…A recent study demonstrated that the GAA⅐TTC repeat observed in Friedreich ataxia and the CTG repeat characteristic of myotonic dystrophy are unstable during passage of human iPSCs or human embryonic stem cells (26,28). Both repeat expansions are very large (ϳ100 to ϳ1000 bp) in the noncoding regions, and instability with maternal transmission of the expanded allele has been described (44,45). The mismatch repair enzyme MSH2, which is up-regulated during reprogramming, has been implicated in GAA⅐TTC repeat instability.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that the GAA⅐TTC repeat observed in Friedreich ataxia and the CTG repeat characteristic of myotonic dystrophy are unstable during passage of human iPSCs or human embryonic stem cells (26,28). Both repeat expansions are very large (ϳ100 to ϳ1000 bp) in the noncoding regions, and instability with maternal transmission of the expanded allele has been described (44,45). The mismatch repair enzyme MSH2, which is up-regulated during reprogramming, has been implicated in GAA⅐TTC repeat instability.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that more than half of the affected mothers do not carry a diagnosis of DM1 because their condition has gone unrecognized, 31 or has not generated any symptoms. 32 Later in childhood, individuals with CDM exhibit delayed motor milestones and a range of learning disabilities, including autism spectrum disorder. 29, 33 Oropharyngeal weakness is prominent, often producing a characteristic tented appearance of the upper lip, facial diplegia, marked dysarthria, and greater impairment of expressive than receptive communication.…”
Section: Congenital Dm1 (Cdm)mentioning
confidence: 99%
“…In the case of autosomal dominant myotonic dystrophy, TRD has been reported in live-born offspring from affected female parents but not affected male parents. [3][4][5] When looking at meioses from unaffected parents heterozygote for different repeat lengths (non-disease causing) at the DM locus, there was a significant distortion in favour of transmission of the larger allele in males. 6 In contrast, no TRD was determined for any allele length when sperm from heterozygous unaffected donors were analysed 7 or when pre-natal diagnoses were analysed from either affected mothers or fathers.…”
Section: Introductionmentioning
confidence: 99%